The words we lost - Deese, Nicole (A fog harbor romance, 2023)
"After Ingrid Erikson jeopardizes her career, she fears her future will remain irrevocably broken. But when the man who shattered her belief in happily-ever-afters offers her a sealed envelope from her late best friend, Ingrid is sent on a hunt for a hidden manuscript and must confront her past before she can find the healing she's been searching for"--